(3CKQ eVj GdeOI aj GdMbhb GdTNUjI (B:s (3OQGSI aj OhQ GdbGVj aj GdTQjYI GdESdGejI hGdbGfhf GdhVYj (B/s - (3GdcHjSj, eMeO QLH HcQjs ((3HjQhJ (B:s (3efThQGJ GdMdHj GdMbhbjI,s, 2015)
(3LGA gPG GdcJGH dHjGf eTQhYjI GdbVGA hTQhWg hJhdjJg hdOQGSI GdWHjYI GdTQYjI hGdbGfhfjI deQhQ GdReGf heOO eQhQ GdReGf aj Gdabg GdESdGej hGdbGfhf GdhVYj (B((3Gdabg GdeGdcj hGdabg GdMfaj(B) (3hMSGH eOO GdJbGOe hMSGH eOO GdJbGOe hSQjGfgG hhba GdJbGOe hbWY GdJbGOe hJfGhd GdcJGH CjVG BKGQ eQhQ GdReGf hGdJeSc HGdJbGOe hGdfRhd Yf GdJbGOe hBKGQ GdJbGOe(B.s
(3HHdjhLQGajI (B: (3UaMI (B229-247.s
Keywords: (3GdJbGOe (B((3abg ESdGej(B)s; (3GdGdJRGeGJ (B((3abg ESdGej(B)s; (3GdhbJ (B((3bGfhf(B)s